Construction of Ce(OH)4 nanostructures from 1D to 3D by a mechanical force-driven method1. Issue 13 (7th April 2015) - Tang, Ke; Zhang, Jingcai; Wang, Wenzhi; Wang, Shuping; Guo, Jinxin; Yang, Yanzhao
<x xml:space="preserve">Abstract</x> A simple protocol has been designed to perform a controllable conversion between 1D and 3D nanostructures based on a mechanical force-driven method.